Land Mafia Case Handling Through the Optimalization of Land Mafia Task Force Role - Tehupeiory, Aarce (SASI, 2023)
Introduction: Various aspects regarding the importance of land often become conflicts in the society, such as land ownership status conflict, land tenure status conflict and compensation for land acquisition and usage. The forms of the legal mafia practice are brokers in buying and selling cases, bribes, illegal levies and land mafia due to inaccurate land data.Purposes of the Research: Explaining and analyzing how the state has handled cases of land mafia practices so far and the optimization of the role of the Land Mafia Task Force in preventing and eradicating the practice of the Land Mafia..Methods of the Research: The approach of the research is qualitative, verificative, evaluative, through statutory approach, and case approach. With documentation data collection techniques, audiovisual materials, and supported by interviews.Results of the Research: The handling of cases of land mafia practices through optimizing the role of the Land Mafia Task Force so far has never reflected the principle of prudence and respect for land rights holders. In handling land mafia cases, actions are often done arbitrarily to the detriment of the actual land rights holders that they do not reflect justice, balance, and does not protect the ownerships’ rights. The legal formula optimizes the role of the Land Mafia Task Force in preventing and eradicating land mafia practices, which is the formation of a Special Cross-Ministerial Team and Academics by making SOPs and technical instructions in carrying out activities to prevent and eradicate land mafia.